Plate X from 'An Historical Account of the Campaign in the Netherlands'... - Author: William... (Wikimedia Commons, 1817)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence Public domain via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie